Sleep Duration and Quality as Related to Left Ventricular Structure and Function. Issue 1 (January 2018) - Lee, Jae-Hon; Park, Sung Keun; Ryoo, Jae-Hong; Oh, Chang-Mo; Kang, Jeong Gyu; Mansur, Rodrigo B.; Alfonsi, Jeffrey E.; Lee, Yena; Shin, Sun-Han; McIntyre, Roger S.; Jung, Ju Young
ABSTRACT: Objective: Inadequate sleep is associated with increased risk of cardiovascular events; however, the associations between sleep duration or quality and cardiac function or structure are not well understood. This cross-sectional study was conducted to investigate to what extent sleep duration and quality are associated with left ventricular (LV) diastolic dysfunction or structural deterioration. Methods: A total of 31, 598 healthy Korean adults who received echocardiography and completed the Pittsburg Sleep Quality Index were enrolled in this study. Participants were stratified into three groups by self-reported sleep duration (i.e., <7, 7–9, >9 hours) and into two groups by subjective sleep quality. Sleep duration was also assessed as a continuous variable. The odds ratios for impaired LV diastolic function, increased relative wall thickness, and LV hypertrophy (LVH) were compared between groups using multivariable logistic regression analyses. Results: After adjustment for confounding variables (e.g., age, smoking, body mass index), there was a statistically significant association between short sleep duration (<7 hours) and greater LVH (fully adjusted odds ratio = 1.32 [95% confidence interval CI = 1.02–1.73]). Short sleep duration was also significantly associated with greater LVH (0.87 per hour [95% CI = 0.78–0.98]) and increased relative wall thickness (0.92 [95% CI = 0.86–0.99]), but there was no significant association between sleep and LV diastolic function. Among individuals with normal sleep duration, poor quality of sleep was not associated with adverse cardiac measures. Conclusions: These results indicate that short sleep duration (<7 hours) is associated with unfavorable LV structural characteristics. The association of insufficient sleep with adverse cardiovascular health outcomes may be mediated in part by adverse changes in cardiac structure and function. Abstract : Supplemental digital content is available in the text.